A patient with a curious case of cyclical vomiting. Issue 2 (February 2017) - Smith, David A.; Phillips, Hayden R.
Abstract : ABSTRACT: Cannabis-related ED visits are on the rise due to wider legalization and availability of marijuana, and habitual daily use is increasingly common. Cannabis abuse has long been associated with various short-term and long-term adverse reactions. One such reaction is cannabinoid hyperemesis syndrome: cyclical vomiting, nausea, and abdominal pain that only resolves with a warm bath or shower. Healthcare providers must understand the signs and symptoms of cannabinoid hyperemesis syndrome so the problem can be recognized early and patients avoid unnecessary testing.